ANALISIS KORELASI ANTARA MOTIVASI DENGAN KEPUASAN KERJA KARYAWAN BANKALTIM CABANG SANGATTA - Marisa, Marisa (PREDIKSI, 2016)
This study aims to determine the level of employee motivation, employee satisfaction levels and the correlation between motivation and job satisfaction of employees Bankaltim Sangatta Branch. This study uses a quantitative descriptive approach. The results showed that there is a significant relationship between the variables of motivation satisfaction variables. This can be seen from the calculation of product moment correlation coefficient rs empirical yield of 0,795 is greater than the theoretical rs amounted to 0,388. The results showed also that the value of R-Square is 0.632, which means that the contributions made by the variable work motivation on job satisfaction variables amounted to 63.2%. This means it can be concluded that the motivation variable correlated positively and significantly with the variable employee satisfaction. Thus it can be said that the hypothesis that the writer formulated in this study can be received and verified.Â